2007
DOI: 10.1890/06-0685
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Aural Detections of Songbirds

Abstract: Many factors affect the number of birds detected on point count surveys of breeding songbirds. The magnitude and importance of these factors are not well understood. We used a bird song simulation system to quantify the effects of detection distance, singing rate, species differences, and observer differences on detection probabilities of birds detected by ear. We simulated 40 point counts consisting of 10 birds per count for five primary species (Black-and-white Warbler Mniotilta varia, Black-throated Blue Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 26 publications
3
133
0
Order By: Relevance
“…8). Logistic regression (Alldredge et al 2007b). Note the consistent effect of singing rate on detection probability analyses indicated that species, singing rate, distance, and observer were all significant factors affecting detection probabilities.…”
Section: Factors Affecting Detection Probabilitiesmentioning
confidence: 91%
See 3 more Smart Citations
“…8). Logistic regression (Alldredge et al 2007b). Note the consistent effect of singing rate on detection probability analyses indicated that species, singing rate, distance, and observer were all significant factors affecting detection probabilities.…”
Section: Factors Affecting Detection Probabilitiesmentioning
confidence: 91%
“…Our approach uses empirical data from field studies of southern Appalachian songbirds (Shriner 2001;Lichstein et al 2002;Brewster 2007) to inform the development of new avian sampling methods Alldredge et al 2007a), and to design field experiments (Simons et al 2007) that assess the factors affecting detection probabilities on auditory counts (Alldredge et al 2007b; Field experiments are conducted using a system for simulating avian census conditions when most birds are identified by sound (Fig. 3).…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…[24]. Surveys are often conducted by different observers, and observer ability, age, and experience affect detectability [25,26]. These factors can also impact whether or not a species is identified correctly, which can result in false positives.…”
Section: Origins Of Imperfect Detectionmentioning
confidence: 99%